The Comic Art of Jane Austen: A New Approach Vs The Theme of Pride and Prejudice - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education; Vol 10 No 1 (2025): Journal of Advanced Research in English and Education, 2025)
Jane Austen’s “Pride and Prejudice” is a masterpiece of social commentary and character study, traditionally analyzed through the thematic lens of pride, prejudice, and societal expectations. However, a fresh perspective emerges when we examine Austen’s work through the lens of her comic artistry. This article aims to explore how Austen’s masterful use of wit, irony, and satire serves not only to entertain but also to deepen our understanding of her characters and their moral dilemmas. By analyzing specific instances of comic portrayal, we can see how Austen subtly critiques the follies of her characters while simultaneously engaging the reader in a delightful and insightful narrative. This approach allows us to appreciate the nuanced layers of humor that permeate the novel, revealing a sophisticated comic structure that complements and enhances the more traditionally recognized themes. We argue that Austen’s comic art is not merely a stylistic flourish but a fundamental tool for conveying her moral vision. By juxtaposing the comedic elements with the central themes of pride and prejudice, we can gain a more comprehensive understanding of Austen’s genius and her enduring relevance. This article will dissect ten key comic elements, each linked to the character development and narrative progression, ultimately showcasing how Austen’s comic genius provides a crucial key to unlocking the novel’s enduring appeal.